Human population structure of the Costa Rican Central Provinces. An evaluation through isonymic methods - Sáenz, Andrés E (2009)
The human population structure of the Central Provinces of Costa Rica was analyzed through isonymic methods and the use of Electoral Registers (1990 and 2006). Four parameters that define, in a genetic and evolutionary context, this structure were estimated: the consanguinity due to random mating (Morton’s a-priori kinship Fii), the genetic isolation (Fisher’s α), the migration (Karlin-McGregor’s υ), and the degree of subdivision or population differentiation (Fst). The possible geographical distribution of these variables is shown by the use of a Principal Components Analysis (PCA). There is a coincidence between groups of counties obtained by similarity in surname diversity and their geographic location in the territory. Differences were found for the values of the components of consanguinity (F=15.6; p<0.05) and genetic isolation (F=14.38; p<0.05) between different sectors of the Central Provinces. There is an association between population density and the breaking up of genetic isolates and another possible association between the geography of the region, the migration patterns of individuals, and the consequent levels of inbreeding and genetic isolation. The differences in the values of population structure components, inbreeding and genetic isolation, between the different zones of the central region, allow the assumption of the existence of differences in gene frequencies. The migration of blocks of genes from the center to the periphery is also possible and the variation in this sense might be attributed mostly to changes in the components of the population structure: mating patterns, migration and the consequence of the effective population size in the genetic drift process.